Synthetic inhibitor leads of human tropomyosin receptor kinase A (hTrkA). Issue 3 (10th January 2020) - Subramanian, Govindan; Vairagoundar, Rajendran; Bowen, Scott J.; Roush, Nicole; Zachary, Theresa; Javens, Christopher; Williams, Tracey; Janssen, Ann; Gonzales, Andrea
Abstract : New h TrkA kinase domain type 2 inhibitors and mixed type 1/type 2 inhibitor leads disclosed here offers a differential starting point to investigate the disease pathophysiology. Abstract : In silico virtual screening followed by in vitro biochemical, biophysical, and cellular screening resulted in the identification of distinctly different h TrkA kinase domain inhibitor scaffolds. X-ray structural analysis of representative inhibitors bound to h TrkA kinase domain defined the binding mode and rationalized the mechanism of action. Preliminary assessment of the sub-type selectivity against the closest h TrkB isoform, and early ADME guided the progression of select inhibitor leads in the screening cascade. The possibility of the actives sustaining to known h TrkA resistance mutations assessed in silico offers initial guidance into the required multiparametric lead optimization to arrive at a clinical candidate.